Congenital tuberculosis in an extremely preterm infant conceived after in vitro fertilization: case report. Issue 1 (December 2017) - Samedi, Veronica; Field, Stephen; Al Awad, Essa; Ratcliffe, Gregory; Yusuf, Kamran
Abstract Background Congenital tuberculosis is a rare manifestation of tuberculosis. The diagnosis is often delayed, especially in preterm neonates because of the non-specific clinical presentation and the lack of awareness of maternal disease prior to pregnancy. Case Presentation We report a case of congenital tuberculosis in an infant born at 24 weeks of gestation to a mother who presented with uncontrolled seizures during preterm labor. Maternal diagnosis was initially made by placental pathology, and later confirmed by isolation of Mycobacterium tuberculosis in urine, gastric aspirates and sputum. Full screening was performed on the newborn infant, and both mother and infant were successfully treated for tuberculosis with a four drug regimen. Conclusion Pregnancy can exacerbate latent tuberculosis and women originating from endemic areas are especially susceptible. The best way to prevent congenital tuberculosis is to have a high index of suspicion and identify and treat tuberculosis in pregnant women.